Regional input-output tables and models - Sargento, Ana (2017)
The present research concerns the study of input-output modelling and input-output table construction, when applied at the regional level. Input-output models, at the national or regional level, are known as a fundamental tool for economic analysis. Yet, in order to apply such models, the researcher must have access to the correspondent input-output tables. National-level tables are currently published by the national statistical offices according to well-defined conventions. The same, however, cannot be said about regional tables which are not provided as a rule by official statistics organisms. Being so, a great part of input-output research is still dedicated to the study of techniques for input-output table gathering. This dissertation is, in such context, divided into three chapters. The first one is mainly theoretical, aiming to review the basic principles underlying input-output analysis at the regional level. The second and third chapters constitute the research’s practical contribution, focused on two major issues, respectively: 1) interregional trade estimation and 2) input-output modelling on the basis of total-use rectangular table at purchasers’ prices. In most countries, survey-based interregional trade data does not exist. However, even when some simplifying assumptions are used in the model, a minimum amount of data on interregional trade is always necessary, in order for the model to succeed in capturing spillover and feedback effects caused by the interregional linkages. In order to evaluate the reasonability of using indirect interregional trade flows estimates, a comparison was made between alternative methodologies (with special focus on gravitational models), assessing the sensitivity of the model results. Such comparison allowed to conclude that the results of the input-output model are not greatly affected by the insertion of different trade flow values. Thus, the results obtained do not reject the reasonability of using indirect estimates for interregional trade, whenever survey-based data is unavailable. The official input-output tables are published on a total-use rectangular format, which is different from the lay-out upon which traditional input-output models were developed (domestic use symmetric tables). The objective here was to demonstrate the equivalence in the results of the input-output model between two alternative procedures: 1) to convert the available input-output table into a domestic-flow symmetric table at basic prices and then implement the input-output model; 2) to perform the direct modelling of the original table (the total-flow rectangular table at purchasers’ prices). It has been concluded that, when the same set of hypotheses is used, there is no advantage in making a previous transformation of the original tables into the symmetric format and a previous calculation of domestic flows, since the results of the model are exactly the same.